Pengaruh Profitabilitas, Likuiditas, Dan Ukuran Perusahaan Terhadap Struktur Modal - Sayyid Ramadhan Z.A; Zulpahmi Zulpahmi; Sumardi Sumardi (STIE Jambatan Bulan, 2021)
This research uses secondary data, namely the financial position report, and the financial ratios report obtained from the respective companies ' websites which are sampled in this study. The X variables examined in this study were the profitability, liquidity, and size of the company while the Y variable in this study was the capital structure. The data processing and analysis techniques used in this study are accounting analysis, classical assumption test (normality test, multicolinearity test, heteroskedasity test, autocorrelation test), double linear regression analysis, hypothesis test, and coefficient of determination analysis